Demystifying the spontaneous phenomena of motor hyperexcitability. Issue 8 (August 2021) - Bashford, J.; Chan, W.K.; Coutinho, E.; Norwood, F.; Mills, K.; Shaw, C.E.
Highlights: Fasciculation, myokymia and neuromyotonia are the core spontaneous phenomena of motor hyperexcitability. Accurate characterisation is particularly important in amyotrophic lateral sclerosis, Isaacs syndrome and Morvan syndrome. Advanced quantification by high-density surface electromyography could enhance biomarker development and therapeutic monitoring. Abstract: Possessing a discrete functional repertoire, the anterior horn cell can be in one of two electrophysiological states: on or off. Usually under tight regulatory control by the central nervous system, a hierarchical network of these specialist neurons ensures muscular strength is coordinated, gradated and adaptable. However, spontaneous activation of these cells and their axons can result in abnormal muscular twitching. The muscular twitch is the common building block of several distinct clinical patterns, namely fasciculation, myokymia and neuromyotonia. When attempting to distinguish these entities electromyographically, their unique temporal and morphological profiles must be appreciated. Detection and quantification of burst duration, firing frequency, multiplet patterns and amplitude are informative. A common feature is their persistence during sleep. In this review, we explain the accepted terminology used to describe the spontaneous phenomena of motor hyperexcitability, highlighting potential pitfalls amidst a bemusing and complex collection of overlapping terms. We outline the relevance of these findings within the context of disease, principally amyotrophic lateral sclerosis, Isaacs syndrome and Morvan syndrome. In addition, we highlight the use of high-density surface electromyography, suggesting that more widespread use of this non-invasive technique is likely to provide an enhanced understanding of these motor hyperexcitability syndromes.